Transient Stability Analysis of the Two-Area With AC/DC Paralleled Interconnected Power System in Different Operation - Liu, Hongbo; Zhang, Shuyu; Sun, Li; Zhang, Chong; Peng, Xiaoyu (Frontiers in Energy Research, 2021)
In order to deeply explore the transient stability mechanism of the AC/DC hybrid system, this paper analyzes the rotor angle stability of the two-area AC/DC hybrid system. The system is analyzed after subjecting it to large disturbances in the AC system and for different operating conditions, qualitatively and quantitatively. The influence of factors, such as the AC operating point of the system and the proportion of DC transmission power, have been considered for improving the rotor motion equation. Subsequently, the transient characteristics of the hybrid system are analyzed after being subjected to disturbances. The power angle stability margin index is obtained, based on which the transient characteristics after DC blocking are analyzed, and the coordinated control strategy with the least control cost is proposed. The results are verified using the two-area AC/DC parallel transmission system network model. The study provides the reference for ensuring the security and stability of the hybrid AC/DC power grid.